Common non infectious skin conditions of laboratory mice and rats - GOURTSAS (K.I. ΓΚΟΥΡΤΣΑΣ) K. I. (Journal of the Hellenic Veterinary Medical Society, 2018)
Laboratory mice and rats are the most favourite animals of the researchers all over the world. Sometimes these rodents can show a number of non infectious conditions concerning their hair, skin or legs and tail. These can be alopecia, bite wounds or the shedding of their legs or tail. It is important that ordinarily there is not a pathological cause for these conditions. It is believed that the social behaviour and the enviromental conditions of the animals may play a role. Fortunately, these cases are easily encountered and so, healthy animals are ensured for every reliable research.